Economic nationalism in old and new states - Chicago; Johnson, Harry G. (London ; Allen & Unwin, 1968)
These studies, organized by a committee at the University of Chicago, demonstrate the comparative approach to an economic problem, the relations between economic nationalism and economic development.
Includes bibliographical footnotes and index.
lje 27/07/2018
Loans
Keywords: Economic policy; Nationalism; Developing countries